(untitled) (Fiep Bulletin - online, 2012)
The high prevalence of headache is demonstrated by several studies worldwide. These show a high incidence in men and women of all ages. Headache is a symptom frequently encountered in clinical practice, it is estimated that its prevalence suggests that 80% of the population will suffer from headache in a certain phase of life. Currently, one can find various treatments that seek to alleviate the headache due to the high incidence in the population. Manual therapy is a set of techniques applied through the hands of the therapist, including mobilization and muscle and joint manipulations, which have been applied by physical therapists, chiropractors and osteopaths. The use of manual therapy as adjuvant treatment for headaches usually shows evidence of improvement. The methodology was defined as an exploratory research and literature, through scientific and theoretical articles. The research showed that manual therapy techniques used in the treatment of headache provide improved clinical course of patients treated by relieving and / or reducing the intensity, frequency and duration of pain with consequent improvement in quality of life of patients treated.